Comparison of Sustained Hemodiafiltration with Acetate-Free Dialysate and Continuous Venovenous Hemodiafiltration for the Treatment of Critically Ill Patients with Acute Kidney Injury - Masanori Abe; Noriaki Maruyama; Shiro Matsumoto; Kazuyoshi Okada; Takayuki Fujita; Koichi Matsumoto; Masayoshi Soma (International Journal of Nephrology)
We conducted a prospective, randomized study to compare conventional continuous venovenous hemodiafiltration (CVVHDF) with sustained hemodiafiltration (SHDF) using an acetate-free dialysate. Fifty critically ill patients with acute kidney injury (AKI) who required renal replacement therapy were treated with either CVVHDF or SHDF. CVVDHF was performed using a conventional dialysate with an effluent rate of 25 mL⋅kg−1⋅h−1, and SHDF was performed using an acetate-free dialysate with a flow rate of 300−500 mL/min. The primary study outcome, 30 d survival rate was 76.0% in the CVVHDF arm and 88.0% in the SHDF arm (NS). Both the number of patients who showed renal recovery (40.0% and 68.0%, CVVHDF and SHDF, resp.; P<.05), and the hospital stay length (42.3 days and 33.7 days, CVVHDF and SHDF, resp.; P<.05), significantly differed between the two treatments. Although the total convective volumes did not significantly differ, the dialysate flow rate was higher and mean duration of daily treatment was shorter in the SHDF treatment arm. Our results suggest that compared with conventional CVVHDF, more intensive renal support in the form of post-dilution SHDF with acetate-free dialysate may accelerate renal recovery in critically ill patients with AKI.